Question:

How to prove <span title="sin(x+y)=sinxcosy+cosxsiny?">sin(x+y)=sinxcosy+cosxsin...</span>

by  |  earlier

0 LIKES UnLike

thank you very much

 Tags:

   Report

3 ANSWERS


  1. If you could tell me what level of math this is for, I will think about it for you.  The method I know uses exponential and imaginary numbers, but you may be at a different math level.  I want to help you the correct way. Please let me know.  Thanks.


  2. I&#039;ll try to explain it to you, though it&#039;s quite hard without drawing....

    (the proof is somewhat complicated...)

    Imagine the trigonometric circumference: as you know, any arc begins at A Ξ (1;0); then consider the arcs x and y (assuming x &gt; y), whose ending points (belonging to the trigonometric circumference), X and Y, respectively, have the following coordinates:

    X Ξ (cosx; sinx)

    Y Ξ (cosy; siny)

    then imagine to draw the arc (x - y) beginning at A Ξ (1;0) and ending at B Ξ (cos(x - y); sin(x - y))

    well, due to the construction, the chords XY and AB are equal to each other:

    XY = AB

    then, recalling the evaluation of the distance between two points as a

    function of their coordinates, you get:

    XY = √[(cosx - cosy)² + (sinx - siny)²]

    AB = √{[cos(x - y) - 1]² + [sin(x - y) - 0]²} = √{[cos(x - y) - 1]² + sin²(x - y)}

    thus equating them, you get:

    XY = AB →

    √[(cosx - cosy)² + (sinx - siny)²] = √{[cos(x - y) - 1]² + sin²(x - y)} →

    squaring both sides:

    (cosx - cosy)² + (sinx - siny)² = [cos(x - y) - 1]² + sin²(x - y) →

    expanding the squares:

    cos²x - 2cosx cosy + cos²y + sin²x - 2sinx siny + sin²y = cos²(x - y) - 2cos(x - y) +

    1 + sin²(x - y) →

    note that:

    cos²(x - y) + sin²(x - y) = 1 (pythagorean identity)

    cos²x + sin²x = 1

    cos²y + sin²y = 1

    therefore:

    1 - 2cosx cosy + 1 - 2sinx siny  = 1 - 2cos(x - y) + 1  ÃƒÂ¢Ã‚†Â’

    2 - 2cosx cosy - 2sinx siny  = 2 - 2cos(x - y)  ÃƒÂ¢Ã‚†Â’

    - 2cosx cosy - 2sinx siny  = - 2cos(x - y)  ÃƒÂ¢Ã‚†Â’

    dividing both sides by (- 2):

    cosx cosy + sinx siny  = cos(x - y)

    that is the cosine subtraction rule indeed;

    in order to get sine addiction rule from this, simply replace x with u = (π/2) - x, yielding:

    cos(u - y) = cosu cosy + sinu siny  ÃƒÂ¢Ã‚†Â’

    cos[(π/2) - x - y] = cos[(π/2) - x] cosy + sin[(π/2) - x] siny  ÃƒÂ¢Ã‚†Â’

    cos[(π/2) - (x + y)] = cos[(π/2) - x] cosy + sin[(π/2) - x] siny  ÃƒÂ¢Ã‚†Â’

    recall the identities:

    cos[(π/2) - α] = sinα

    sin[(π/2) - α] = cosα

    thus, in conclusion:

    sin(x + y) = sinx cosy + cosx siny

    your identity being proved

    I hope it helps...

    Bye!!


  3. this actually came from the formula of addition for cosine .. . .

    cos(x ± y) = cosx cosy ∓ sinx siny

    then

    sin(x + y) = cos(π/2 - (x+y)) = cos((π/2 - x) - y)

    = cos(π/2 - x) cosy + sin(π/2 - x) siny

    = sinx cosy + cosx siny

    now, to prove that cos(x + y) = cosx cosy - sinx siny .. . .. .

    this used the distance formula:

    let P(1,0), A(cosx, sinx) , B(cosy, siny) , C(cos(x-y), sin(x-y))

    the angle from the positive x-axis to A is x.

    the angle from the positive y-axis to B is y.

    thus the angle between them is x - y , say, x &gt; y.

    thus the distance bet AB is the same distance as CP

    then

    d(AB) = √[(cosx - cosy)^2 + (sinx - siny)^2]

    = √[cos^2x - 2cosx cosy + cos^2y + sin^2x - 2sinxsiny + sin^2y]

    = √[2 - 2(cosx cosy + sinx siny)]

    meanwhile

    d(CP) = √[(1- cos(x-y)^2 + sin^2(x-y)]

    = √[1 - 2cos(x-y) + cos^2(x-y) + sin^2(x-y)]

    = √[2 - 2cos(x-y)]

    thus

    cos(x - y) = (cosx cosy + sinx siny)

    and the rest follows.

Question Stats

Latest activity: earlier.
This question has 3 answers.

BECOME A GUIDE

Share your knowledge and help people by answering questions.